Influence of nanovoids on α–α′ phase separation in FeCrAl oxide dispersion strengthened alloy. (1st January 2016) - Capdevila, C.; Aranda, M.M.; Rementeria, R.; Domínguez-Reyes, R.; Urones-Garrote, E.; Miller, M.K.
Graphical abstract: The presence of nanovoids in the neighborhood of oxide particles in FeCrAl oxide dispersion strengthened (ODS) alloy has been identified. These nanovoids are inherent to the manufacturing route and remain quite resistant during heat treatments. Positron annihilation spectroscopy (PAS) experiments demonstrate that these nanovoids trap Cr inside thereby reducing the Cr-content in the matrix. This might lead to a delay in the α – α ′ phase separation process as observed by atom probe tomography (APT). Abstract: The presence of nanovoids in the vicinity of oxide particles in FeCrAl oxide dispersion strengthened (ODS) alloy has been identified. These nanovoids are inherent to the manufacturing route and remain quite resistant during heat treatments. Positron annihilation spectroscopy (PAS) experiments demonstrate that these nanovoids trap Cr inside thereby reducing the Cr-content in the matrix. This might lead to a delay in the α – α ′ phase separation process as observed by atom probe tomography (APT).